Marketing Your Business in India: Challenges and Opportunities - Agarwal, Varsha (IJARESM, 2022)
We are witnessing changes in our daily lives in addition to those in the company. Consumer demands for higher levels of dependability and quality in products and services are increasing, new products and services are being introduced to the market more quickly, competition is becoming fiercer and global rather than just domestic, technology is advancing quickly, and e-commerce and the Internet are significantly changing how marketing strategies are executed. In a marketing climate that is changing so fast, business organizations find it exceedingly difficult to respond swiftly and effectively while dealing with a number of marketing challenges. As a result, we are now here to tell you of the marketing challenges that commercial businesses are presently facing as well as the answers to these challenges. Customers have grown accustomed to utilizing different interface technologies, such Websites and cellular devices, to communicate with businesses during the previous ten years. They increasingly decide when and how to interact with businesses for various parts of their interactions. Customers are increasingly using various channels at various points in their decision- and shopping-cycles, such as using websites to gather information but making purchases offline. Previously, they would typically obtain all of their channel services from a single integrated channel at all points in their decision-process.
ISME
Keywords: Marketing; Business; customers; markets; strategies; company